TRANSIENT STABILITY ANALYSIS FOR DETERMINING CRITICAL CLEARING TIME IN ULUMBU GEOTHERMAL POWER PLANT - Aventus Wagur; Abraham Lomi; Irrine Budi Sulistiawati (Merdeka Malang University, 2018)
The presence of 3 comparable phases in the Ulumbu geothermal power plant affects the existing system, so it is necessary to conduct stability analysis to be able to find out the Critical Clearing Time (CCT) of the Circuit Breaker system that can maintain its synchronous condition. The results of the transient system analysis to determine the Critical Clearing Time were carried out when the 3 phases of the Ulumbu geothermal power plant were 0.4 seconds and showed that the level of voltage, frequency, and rotor angle would be faster DOI : https://doi.org/10.26905/jeemecs.v1i2.2353